Aspectos reprodutivos e produtivos de carneiros da raça Morada Nova submetidos a níveis crescentes de suplementação concentrada - Silva, Taciane Alves da (2015)
The study was conducted in order to evaluate the effects of different levels of concentrated supplementation on body weight, seminal parameters, testicular biometry measurements, protein profile of seminal plasma and protein profile of the Longissimus dorsi muscle of the breed of sheep Morada Nova. 22 seven months old sheep were used. The treatments consisted in different levels of concentrated (0%, 0.6%, 1.2% and 1.8% of the animals’ body weight based on dry matter). The animals were kept under a rotational grazing system, on Aruana grass (Panicum maximum). The semen samples were collected through electroejaculation at the end of the experiment, when the animals reached the age of 10 months. After slaughtering, the testicles and the muscle Longissimus dorsi were collected. The testicles were measured and the seminal and muscle proteins were analyzed through two-dimensional electrophoresis in polyacrylamide gel. The proteic maps were analyzed using the PDQuest application, version 8.0; Bio Rad, USA. There were significant differences over body weight and over the expression of the proteic spots of the muscle (P <0.05), but there was no significant difference for the seminal parameters, testicular biometry and the expression of seminal plasma proteins. The spots differentially expressed (P <0.05) were digested with trypsin and subjected to identification through mass spectrometry (ESI-Q-TOF). It is concluded, therefore, that the levels of concentrated provided to the animals change the body weight and influence the expression of the Longissimus dorsi muscle proteins, but do not modify the testicular biometry, the seminal parameters and the expression of seminal plasma proteins.